Teaching and incentives: Substitutes or complements?. (December 2022) - Allen, James; Mahumane, Arlete; Riddell, James; Rosenblat, Tanya; Yang, Dean; Yu, Hang
Abstract: Interventions to promote learning are often categorized into supply- and demand-side approaches. In a randomized experiment to promote learning about COVID-19 among Mozambican adults, we study the interaction between a supply and a demand intervention, respectively: teaching via targeted feedback, and providing financial incentives to learners. In theory, teaching and learner-incentives may be substitutes (crowding out one another) or complements (enhancing one another). Experts surveyed in advance predicted a high degree of substitutability between the two treatments. In contrast, we find substantially more complementarity than experts predicted. Combining teaching and incentive treatments raises COVID-19 knowledge test scores by 0.5 standard deviations, though the standalone teaching treatment is the most cost-effective. The complementarity between teaching and incentives persists in the longer run, over nine months post-treatment.